Utopie postcoloniali: Small Island di Andrea Levy (Altre Modernità, 2019)
Postcolonial utopia is a notion only recently explored, connecting the original meaning of utopia as a literary genre concerned with hope for a better world to contemporary postimperial conditions. This article reads Andrea Levy’s successful novel Small Island (2004) as a postcolonial utopia. The interaction of stories Small Island develops mirrors the rise of postwar multiracial and multicultural Britain. Levy’s work conveys a counternarrative reshaping the relationships between colonizers and colonized, black and white subjectivities in the context of Caribbean migrations to the United Kingdom, and, ultimately, reconfigures Britain’s hybrid identity itself. The plot oscillates between 1924 and 1948 and moves across multiple geographical locations: London, rural England, Jamaica, India and the United States. Small Island follows the interwoven stories of Gilbert Joseph, a black Jamaican who joins the RAF during the Second World War and in 1948 arrives in London as an immigrant aboard the Windrush, Hortense Roberts, his Jamaican wife, Queenie Bligh, their white landlady, and Bernard, Queenie’s English husband. The first-person narratives of the four protagonists overlap and intersect; Queenie’s house in Nevern Street, a space shared by the migrants and the English, becomes the point of convergence of multiple, interrelated experiences and, finally, the place of the conception and birth of a mixed-race baby. Queenie’s lodgings represent the re-conceptualization of the British nation as a whole as a utopian site. The “happy ending” suggesting the centrality of a hybrid family structure thanks to a deep solidarity between whites and blacks seems to overcome racial discrimination and cultural and emotional dislocation, and to create a new rhetoric of national belonging.